2016
DOI: 10.1089/thy.2016.0038
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Radioactive Iodine Administration Does Not Influence Outcomes in Patients with Differentiated Thyroid Carcinoma

Abstract: Timing of RAI does not seem to interfere with the disease outcomes in DTC and can therefore be safely planned while taking into account the health system logistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…Scheffel et al demonstrated that the time between total thyroidectomy and RAIT does not interfere with the response to initial therapy, disease status at follow‐up and recurrence rate in patients with DTC. In their study, 45% and 13% of patients were at intermediate and high risk, respectively . Suman et al also showed that the timing of first post‐thyroidectomy RAIT did not affect survival in a propensity score‐matched cohort with high‐risk PTC using National Cancer Database.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Scheffel et al demonstrated that the time between total thyroidectomy and RAIT does not interfere with the response to initial therapy, disease status at follow‐up and recurrence rate in patients with DTC. In their study, 45% and 13% of patients were at intermediate and high risk, respectively . Suman et al also showed that the timing of first post‐thyroidectomy RAIT did not affect survival in a propensity score‐matched cohort with high‐risk PTC using National Cancer Database.…”
Section: Discussionmentioning
confidence: 99%
“…While assessing the impact of the timing of the first post-thyroidectomy RAIT is critical for planning treatment for patients requiring this therapeutic modality, it remains unclear whether early RAI administration after thyroidectomy is associated with better clinical outcomes. [6][7][8][9][10] Consequently, the current guidelines lack definite recommendations regarding the optimal time for RAI administration after surgery. 1,11 The time of initiating the first post-thyroidectomy RAI varies worldwide and may be affected by personal, social-environmental and disease-related factors.…”
mentioning
confidence: 99%
See 3 more Smart Citations